2022
DOI: 10.1186/s13098-022-00946-2
|View full text |Cite
|
Sign up to set email alerts
|

GA/HbA1c ratio is a simple and practical indicator to evaluate the risk of metabolic dysfunction-associated fatty liver disease in type 2 diabetes: an observational study

Abstract: Background It is still debatable whether glycated albumin/glycated hemoglobin A1C (GA/HbA1C) ratio is associated with metabolic dysfunction-associated fatty liver disease (MAFLD), and few studies have been conducted in type 2 diabetes mellitus (T2DM). Therefore, we aimed to investigate the association between GA/HbA1C ratio and MAFLD and to evaluate whether GA/HbA1C ratio can be used an indicator of MAFLD in Chinese patients with T2DM. Methods This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(93 reference statements)
0
1
0
Order By: Relevance
“…However, a previous study showed that in individuals with T2DM, the GA/HbA1c ratio was lower in NAFLD patients than in individuals without NAFLD and was negatively correlated with NAFLD stage [ 15 ]. In addition, among 7,117 patients with T2DM, after adjusting for gender, age, and duration of diabetes, there was a significant downward trend in the prevalence of MAFLD based on the quartiles of GA/HbA1C ratio (the Q1, Q2, Q3 and Q4 were 56.3%, 47.4%, 37.8%, and 35.6%, respectively, P trend < 0.001), indicating a significant negative correlation [ 35 ]. This may be related to the following reasons.…”
Section: Discussionmentioning
confidence: 99%
“…However, a previous study showed that in individuals with T2DM, the GA/HbA1c ratio was lower in NAFLD patients than in individuals without NAFLD and was negatively correlated with NAFLD stage [ 15 ]. In addition, among 7,117 patients with T2DM, after adjusting for gender, age, and duration of diabetes, there was a significant downward trend in the prevalence of MAFLD based on the quartiles of GA/HbA1C ratio (the Q1, Q2, Q3 and Q4 were 56.3%, 47.4%, 37.8%, and 35.6%, respectively, P trend < 0.001), indicating a significant negative correlation [ 35 ]. This may be related to the following reasons.…”
Section: Discussionmentioning
confidence: 99%